Influence of forging conditions on the fatigue mechanisms of low alloy steels: a 3D study - Pablo Lorenzino; Jean-Yves Buffiere; Catherine Verdu (Fracture and Structural Integrity)
The influence of forging conditions on the propagation of physically small fatigue cracks has been studied for two high strength steels. Two surface conditions were produced after the forging process. The subsurface microstructure of the materials has been characterized by EBSD. Small samples extracted from the original specimens were used to perform in situ fatigue tests monitored by high resolution synchrotron X-ray tomography. Fatigue cracks were initiated from an artificial defect (100 μm wide x 50 μm deep) introduced in the forging skin by laser machining. 3D images of the initiation and growth of those physically small fatigue cracks have been obtained. It was found that the presence of a shot-blasted skin containing a hardness and microstructure gradient influences the 3D crack shape during propagation in comparison with the materials without material properties gradient. The 3D crack shapes are rationalized in terms of crack closure effects induced by the forging processes, close to the surface.